2004
DOI: 10.1038/sj.leu.2403547
|View full text |Cite
|
Sign up to set email alerts
|

Is physical fitness decreased in survivors of childhood leukemia? A systematic review

Abstract: The aim of this review is to determine whether physical fitness, assessed by peak oxygen uptake (VO 2peak ) measurement, is reduced in survivors of acute lymphoblastic leukemia (ALL) compared to healthy children. A systematic literature search (up to June 2004) was performed using Medline, Sportdiscus, Cinahl, Embase, Cochrane and PEDro database and reference tracking. The VO 2peak (ml kg À1 min À1 ) reached during a maximal exercise test until volitional exhaustion was used as the main outcome for this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
3
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 35 publications
8
86
3
4
Order By: Relevance
“…77 Cardiorespiratory fitness tends to be reduced in survivors of acute lymphoblastic leukemia. 78,79 This suggests the need for this population group to engage in regular physical activities, with the purpose of increasing their functional capacity or physical fitness. More recent data show that even 5-6 years after cessation of childhood leukemia treatment, there are still clear negative effects on motor performance and physical fitness.…”
Section: Physical Fitness and Cancermentioning
confidence: 99%
“…77 Cardiorespiratory fitness tends to be reduced in survivors of acute lymphoblastic leukemia. 78,79 This suggests the need for this population group to engage in regular physical activities, with the purpose of increasing their functional capacity or physical fitness. More recent data show that even 5-6 years after cessation of childhood leukemia treatment, there are still clear negative effects on motor performance and physical fitness.…”
Section: Physical Fitness and Cancermentioning
confidence: 99%
“…7 A recent systematic review revealed slightly reduced VO 2peak in survivors of childhood leukaemia compared with healthy controls. 8 Although HSCT has been described as the treatmentvariable most consistently associated with reduced VO 2peak following childhood leukaemia, 9 only three older studies in a limited number of patients have investigated exercise capacity at long-term follow-up after paediatric HSCT. They found VO 2peak to be moderately reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Pravidelné pohybové aktivity jsou vhodným prostředkem pro celkové zdraví a zlepšení kvality života jedinců všech věkových skupin. V kontextu osob s onkologickým onemocněním na tuto skutečnost upozorňuje také řada dalších zahraničních prací (Cox et al, 2009;Hacker, 2008;Luctkar-Flude, Groll, Woodend, & Tranmer, 2009;Van Brussel, Takken, Lucia, van der Net, & Helders, 2005). Pohybové aktivity jsou do značné míry také predikátorem míry zdraví dětí a mládeže (Vanreusel, Renson, & Beunen, 1997;Yang, Telama, Leino, & Viikari, 1999).…”
Section: T Vyhlídal and M Kudláčekunclassified